PENGARUH KESADARAN WAJIB PAJAK, PEMAHAMAN PERATURAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK - Habib, M. Khusnul; Furqon, Imahda Khoiri (JURNAL PERPAJAKAN, 2023)
The purpose of this study was to determine the effect of awareness, understanding of taxation and tax sanctions on individual taxpayer compliance. Included in the type of correlational research because it is useful for testing research hypotheses. The research sample was taken using a simple random sampling method (Simple Random Sampling) with 100 correspondents. After testing the hypothesis, it can be concluded that partially awareness, understanding of taxation and tax sanctions have a positive and significant effect on the compliance of individual taxpayers registered at KPP Pratama North Malang for the 2020 tax year.